Cytotoxicity of resin-based luting cements to pulp cells - Voltolini Pontes, Elaine Cristina [UNESP]; Soares, Diana Gabriela [UNESP]; Hebling, Josimeri [UNESP]; Souza Costa, Carlos Alberto de [UNESP] (Mosher & Linder, Inc, 2014)
Purpose: To evaluate the cytotoxicity of components released from different types of luting cements to two cell lines obtained from pulp tissue. Methods: Three types of luting cements were evaluated, distributed into the following groups: G1 - negative control (no treatment); G2 - resin-modified glass-ionomer cement (Rely X Luting 2); G3 - self-adhesive resin cement (Rely X U200); and G4 - conventional resin cement (Rely X ARC). Standardized cylindrical specimens (14 mm diameter and 1 mm thick) prepared with the dental materials were immersed in culture medium (DMEM) for 24 hours to obtain the extracts (DMEM + components released from the cements). Then, the extracts were applied to cultured odontoblast-like MDPC-23 cells or human dental pulp cells (HDPCs). Finally, cell viability (MTT assay), cell death (Armexin/PI) (Kruskal-Wallis/Mann-Whitney; alpha = 5%) and cell morphology (SEM) were assessed. Cements' components in contact with cells (SEM/EDS) and pH of the extracts were also evaluated. Results: The resin-modified glass-ionomer cement (02) caused the most intense toxic effect to the two cell lines; the cell viability reduction was around 95.8% and 89.4% for MDPC-23 cells and HDPCs, respectively, which was statistically significantly different compared with that of the negative control group (01). Also, a high quantity of particles leached from this ionomeric cement was found on the cells, which showed intense morphological alterations. In the 02 group, 100% necrosis was observed for both cell lines, and an acidic pH was detected on the extract. Conversely, Rely X U200 (G3) and Rely X ARC (G4), which presented low solubility and no alteration in pH, caused only slight cytotoxicity to the cultured cells.